2018
DOI: 10.1186/s12957-018-1515-2
|View full text |Cite
|
Sign up to set email alerts
|

Progress in research on the role of circular RNAs in lung cancer

Abstract: BackgroundCircular RNA (circRNA), as a covalently closed circular RNA molecule, is widely present, which is recognized as a competing endogenous RNA. A large number of differentially expressed circRNAs have been identified and are recognized as potential biomarkers for the diagnosis of tumors.Main bodyCircRNAs play an important role in the regulation of cell signaling pathways. The main biological functions of circRNAs include acting as miRNA sponges, regulating the transcription of the parental genes, and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…CircRNA, a class of enclosed non-coding RNA molecules generated by RNA splicing, function as an miRNA sponge and regulate gene transcription and alternative splicing [18,19,8,13,4,5]. Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers [13,11,10,6,17,9,16,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNA, a class of enclosed non-coding RNA molecules generated by RNA splicing, function as an miRNA sponge and regulate gene transcription and alternative splicing [18,19,8,13,4,5]. Recent studies have confirmed that circRNA is involved in the regulation of gene expression by various means, thereby indirectly participating in the occurrence and development of various solid cancers [13,11,10,6,17,9,16,14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circRNA can directly bind to proteins, or establish an indirect RNA-mediated association with proteins to influence their functions [8]. Studies have reported that circRNA is closely correlated with the occurrence and development of various malignant tumors, including liver cancer [9,10], lung cancer [11,12], cervical cancer [13] gastric cancer [14,15], colorectal cancer [16,17], etc. In recent years, the potential applications of circRNA in the regulation of biological functions and the clinical diagnosis and prognosis of BC have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…30 Increasing evidence suggested that circRNA might participate in the cell proliferation, migration and invasion of lung cancer, and serve as an important diagnostic marker for the treatment of lung cancer. [31][32][33][34][35][36][37] For example, circNOL10 increased the expression of transcription factor sex comb on midleg-like 1 (SCML1) by inhibiting ubiquitination and regulating the humanin (HN) polypeptide family through affecting multiple signaling pathways. This ultimately inhibited proliferation and induced cell cycle arrest in lung cancer cells.…”
Section: Acting As Autophagy Regulatormentioning
confidence: 99%
“…6,7 In addition, circRNA can directly bind to proteins, or establish an indirect RNA-mediated association with proteins to influence their functions. 8 Studies have reported that circRNA is closely correlated with the occurrence and development of various malignant tumors, including liver cancer, 9,10 lung cancer, 11,12 cervical cancer 13 gastric cancer, 14,15 colorectal cancer, 16,17 etc. In recent years, the potential applications of circRNA in the regulation of biological functions and the clinical diagnosis and prognosis of BC have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%